Kepatuhan Medikasi Penderita Diabetes Mellitus Berdasarkan Teori Health Belief Model (HBM) Di Diabetes Center Kota Ternate Tahun 2017 - Muhlisa Muhlisa; Amira BSA (Interest : Jurnal Ilmu Kesehatan, 2018)
Background: Riskesdas in 2013, North Maluku Province is one of the areas in Indonesia with the prevalence of Diabetes Mellitus (DM) of 1.1%. Data obtained from Diabetes Centre registers, from January to June 2017, the average patient DM visiting are 126 each month. Efforts have been made by the government in tackling the DM problem, but cases in Indonesia are still high. The study used the Health Belief Model (HBM) approach developed by Rosentock and Becker in 1974. HBM is a conceptual framework for understanding individual health behaviors. The purpose of this study is the identification of the perceptual factors of susceptibility, seriousness, benefits, obstacles and family support factors to compliance medication DM patients in the work area of Diabetes Center Ternate City in 2017. Method: using cross sectional approach with Sample amounted to 98 respondents. Instruments using Knowledge and Perception Questionnaire were analyzed using Chi Square test. Results: obtained are almost all respondents have perceptions of vulnerability, seriousness, benefits and obstacles are positive, as well as medication compliance, while for more family support is lacking. Conslusions: Statistical test result there is no correlation between perception of susceptibility, seriousness and benefit with medication compliance whereas perception of obstacles showed significant relationship.